### Home > CC4 > Chapter 7 > Lesson 7.1.2 > Problem 7-27

7-27.

Solve each system. Homework Help ✎

6

*x*− 2*y*= 10

*3x*− 2 =*y*3

*x*− 9*y*= 3

*2x*= 16 −*y**y*= 3*x*+ 1

*x*+ 2*y*= −52

*x*+ 3*y*= 9

*x*− 2*y*= 1

Read Math Notes box in Lesson 6.2.3 on the substitution method.

There is no solution.

Solve the lower equation for *y*, and then substitute the expression for *y* into the top equation and solve.

Substitute 3*x* + 1 for *y* in the second equation.

(−1, −2)

Multiply the entire second equation by −2

Add the equations together.

(3, 1)